1993
DOI: 10.1116/1.586933
|View full text |Cite
|
Sign up to set email alerts
|

Effect of lanthanum doping on the electrical properties of sol-gel derived ferroelectric lead–zirconate–titanate for ultra-large-scale integration dynamic random access memory applications

Abstract: Thin films of lead–zirconate–titanate [(PZT) Pb(Zr0.5Ti0.5)O3] possess demonstrably adequate charge storage densities and endurance to read/write cycling for ultra-large-scale integration dynamic random access memory (DRAM) applications. Lanthanum (donor) doping is expected to reduce the (p-type) conductivity to acceptable levels (<10−6 A/cm2). In this study, six thin films of 200 nm sol-gel derived lanthanum-doped PZT, with the [La]/([La]+[Pb]) concentration ratio varying from 0 to 0.23, have been exam… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

1994
1994
2023
2023

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 40 publications
(5 citation statements)
references
References 0 publications
0
5
0
Order By: Relevance
“…A gradual reduction in the average doping level is observed as more niobium is added to the samples. It has been reported that PZT has p-type conductivity[57] and niobium is an n-type dopant for PZT124]. The compensation of p-type PZT doping by the n-type niobium is supported by the result shown inFig.…”
mentioning
confidence: 71%
“…A gradual reduction in the average doping level is observed as more niobium is added to the samples. It has been reported that PZT has p-type conductivity[57] and niobium is an n-type dopant for PZT124]. The compensation of p-type PZT doping by the n-type niobium is supported by the result shown inFig.…”
mentioning
confidence: 71%
“…Although the origin of the observed leakage is not known, several mechanisms, including Schottky emission, [9][10][11] Frenkel-Poole emission, 12 and space-chargelimited currents ͑SCLC͒, 13,14 may simultaneously contribute to leakage with one of them playing the main role.…”
Section: Mechanisms Of Leakagementioning
confidence: 99%
“…It is evident that the magnitude of bit " 0 relaxation is fairly independent of rise-time. Lanthanum doping causes a reduction in polarization as explained in [8] but also a simulataneous drop in bit "0" relaxation values. The values of Pup and Pdown for rise-times below -1ps are not reliable due to R-C limitations of the circuit.…”
Section: Polarization Dispersion and Relaxationmentioning
confidence: 96%